EFFECT OFWOOD SMOKE ON SELECTED BLOOD ANTIOXIDANT PARAMETERS, ESSENTIAL AND HEAVY METAL LEVELS IN WOMEN - Olufunsho, Odewusi Odeyinka; Abimbola, Tope-Ajayi Ayodele; Olajide, Alabi Gbolahan (European Scientific Journal, ESJ, 2015)
The study was set to assess the effect of exposure to firewood smoke on the levels of essential trace, toxic elements and antioxidant parameters in exposed adult female subjects. A total of 90 blood samples were collected. 60 samples were collected from women who in the process of using firewood as a means of domestic fuel are exposed to the smoke. The remaining 30 were women who are not exposed to wood smoke, these served as control. Determinations of essential Trace metals (Copper, Zinc, and selenium), Heavy metals (Arsenic, cadmium, lead and, mercury) and antioxidant parameters (Superoxide dismutase [SOD] and Thiobarbituric acid reducing substances [TBARS]) was carried out on all blood samples, the result of which was subjected to statistical analysis. The student’s t test was the tool of choice and significance was tested at P<0.05. All heavy metals determined were significantly elevated while all essential trace elements were significantly lowered in subjects constantly exposed to smoke. The mean SOD was found to be significantly lower while TBARS was significantly lower in exposed subjects. It appears that the use of firewood as a means of household fuel exposes these subjects under examination to agents that cause oxidative stress. This research also goes further to confirm that exposure to gaseous products of wood combustion has a depleting effect on the essential trace element levels and antioxidant system and therefore deleterious to human health. It is also associated with an increase in blood levels of toxic metals .